Frequency of Various Etiological Causes of Intestinal Obstruction in Children - Aamir Farooq, Maria Malik, Azhar Hayat, Misbah Abbas, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the frequency of causes of intestinal obstruction among children. Study design: This is a cross sectional study. Place and duration of study: This study was conducted in Allama Iqbal Memorial Teaching Hospital Sialkot. Study was completed in six months duration from January 2022 to June 2022. Methodology: Children with age <12 years admitted in the department of pediatrics and undergoing exploratory laparotomy for intestinal obstruction and fulfilling inclusion criteria were included in this study. On exploratory laparotomy causes of intestinal obstruction were noted like adhesions, intussusceptions, round worms and obstructed hernia. Collected data was analyzed using SPSS version 20 software. Percentages, means and standard deviations were determined. Results: Total 170 cases were studied including 107(62.9%) males and 63(37.1%) females. Range of the ages was one month to 12 years with mean age of 4.37±2.6 years. Most common cause of intestinal; obstruction was adhesions followed by intussusception found in 71(41.7%) and 55(32.3%) cases respectively. Conclusion: Frequency of etiological causes of intestinal obstruction varies in different age groups in children, however adhesions are most common cause of intestinal obstruction in children, while intussusception is second most common cause. Key words: Intestinal obstruction, Adhesion, Intussusception, Etiological causes, Children